Analysis of the Impact of Large Container Ships on Port Capacity - Zhang, Meng (Journal of Theory and Practice of Management Science, 2024)
Facing the fierce competition in the shipping market, major container liner companies are constantly increasing the scale of container ship construction in pursuit of scale effect, and the trend of large-scale development of container ships is increasingly obvious. The enlargement of container ships not only intensifies the competition of shipping companies, but also brings profound changes to the port's facilities and equipment. This paper analyzes the development process, background and reasons of the large-scale container ships, as well as the future development trend of large-scale ships. The qualitative and quantitative method was used to analyze the current status of ship enlargement on the development status. Through the corresponding data and cases, combined with the current rise of international trade protectionism and the global spread of new pneumonia, the impact of ship enlargement on port development was analyzed with a view to the port Development provides corresponding theoretical references and suggestions.